SELF-REGULATED LEARNING DENGAN RESILIENSI AKADEMIK PADA MAHASISWA YANG BEKERJA: STUDI DITINJAU DARI JENIS KELAMIN: Studi Ditinjau dari Jenis Kelamin - Liuw, Lidya Shekinah Glory; Kristinawati, Wahyuni (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
This study aims to examine the relationship between self-regulated learning (SRL) and academic resilience among university students who are simultaneously studying and working, as well as to analyze this relationship separately for male and female students. The research employed a quantitative correlational design. The sample consisted of 200 actively enrolled working students, selected using a snowball sampling technique. Instruments used were the Self-Regulated Learning Scale (SRLS) and the Academic Resilience Scale (ARS-30). Analysis using Spearman’s rho correlation test revealed a positive and significant relationship between SRL and academic resilience. Further analysis showed that this relationship was stronger among female students compared to their male counterparts. These findings highlight the importance of self-regulatory abilities in supporting academic resilience among working students and suggest the need for gender-sensitive approaches in developing academic support programs.